2014
DOI: 10.4306/pi.2014.11.3.258
|View full text |Cite
|
Sign up to set email alerts
|

The Validities and Efficiencies of Korean ADHD Rating Scale and Korean Child Behavior Checklist for Screening Children with ADHD in the Community

Abstract: ObjectiveThe purpose of this study is to examine the validity of primary screening tools for attention deficit hyperactivity disorder (ADHD) in a community-based sample of children using the Korean version of the Child Behavior Checklist (K-CBCL) and the Korean version of the ADHD Rating Scale (K-ARS).MethodsA large-scale community-based study for ADHD screening was conducted in the Jeollabuk province in the Republic of Korea. In 2010-2011, we surveyed a total of 49,088 first- and fourth-grade elementary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Figure 2b plots the results for each study. We see clear differences among studies with the best results being obtained by Fabiano et al [30] and Pineda et al [32] and the worst results being reported by Tripp et al [33] and Park et al [36]. …”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Figure 2b plots the results for each study. We see clear differences among studies with the best results being obtained by Fabiano et al [30] and Pineda et al [32] and the worst results being reported by Tripp et al [33] and Park et al [36]. …”
Section: Resultsmentioning
confidence: 66%
“…Inspection of Figure 2b shows three samples with fairly large differences in accuracy favoring parents over teachers [3436] and one favoring teachers over parents [31]. Those studies showing the highest levels of accuracy [30 32] show very similar results for parents and teachers.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They are helpful in research and clinical work. Rating scales also help in the treatment planning and ensure accountability in practice 33,34 .…”
Section: Vanderbilt Adhd Diagnostic Rating Scale (Vadrs)mentioning
confidence: 99%